Immigration and the distribution of incomes - Francine D. Blau; Lawrence M. Kahn (Institute for the Study of Labor (IZA), 2012)
We review research on the impact of immigration on income distribution. We discuss routes through which immigration can affect income distribution in the host and source countries, including compositional effects and effects on native incomes. Immigration may affect the composition of skills among the residents of a country. Moreover, immigrants can, by changing relative factor supplies, affect native wage and employment rates and the return to capital. We then provide evidence on the level and recent increases in immigration to OECD countries and on the distribution of native and immigrant educational attainment. We next provide a decomposition of 1979-2009 changes in US wage inequality, highlighting the effects of immigration on workforce composition. We then consider the economic theory of the impact of immigration on income distribution, emphasizing labor market substitution and complementarity between natives and immigrants. Further, by changing job opportunities or child care availability, immigrants can affect family, as well as individual, income distribution. We review research methodologies used to estimate the impact of immigration on the native income distribution. These include the structural approach (estimating substitution and complementarity among factors of production, including capital and labor force groups) as well as the natural experiment approach (seeking exogenous sources of variation in immigration) to studying the labor market. We then discuss evidence on these questions for Austria, Britain, France, Germany, Hong Kong, Israel, Portugal, Spain and the United States, as well as the impact of emigration on source country income distribution.
Keywords: D33; J61; 330; international migration; factor income distribution; Einwanderung; Internationale Wanderung; Funktionelle Einkommensverteilung; Beschäftigungseffekt; Verteilungswirkung; OECD-Staaten; Österreich; Großbritannien; Frankreich; Deutschland; Hongkong; Israel; Portugal; Spanien; USA